Upaya Guru BK Dalam Mengelola Motivasi Belajar Pada Siswa - Chyntia, Caroline; Tyas, Prias Hayu Purbaning (Universitas Sanata Dharma, 2024)
The aims of this study were to: (1) find out the counseling teacher's strategy in increasing student learning motivation at SMKN 5 Yogyakarta. (2) Supporting factors for counseling teachers in increasing student learning motivation at SMKN 5 Yogyakarta. (3) Development of counseling teacher inhibiting factors in increasing student learning motivation at SMKN 5 Yogyakarta (4) Development of counseling teacher inhibiting factors in increasing student learning motivation at SMKN 5 Yogyakarta. This type of research is qualitative research in the form of a case study. Collecting data using in-depth interview techniques and observation of the two respondents. Respondents who were the main respondents were a senior counseling teacher and a junior counseling teacher. The validity used in this study is triangulation in which the researcher checks the results of the data that has been obtained from other sources to ensure that the things asked are true. The qualitative data analysis technique used by the researcher is to make verbatims, make coding from verbatims, then group themes. data filtering, and interpretation. From the results of this study, it was found that (1) the counseling teacher's strategy in increasing student learning motivation was an approach to students and acceptance of students, collaboration between lines such as: homeroom teacher, vice principal, principal, parents, and the community. (2) the supporting factors for counseling teachers in increasing student learning motivation are having an appropriate educational background, interlinear cooperation, and student background. (3) There are inhibiting factors for counseling teachers in increasing student learning motivation, namely the lack of a sense of parental loyalty and the absence of test assessments at school. (4) To overcome this, the counseling teacher immediately moves to the student to help him get the right to learn and maximize the non-test assessment used.